2010
DOI: 10.1017/s1368980010001813
|View full text |Cite
|
Sign up to set email alerts
|

The duration of obesity and the risk of type 2 diabetes

Abstract: Objective: The evidence for the association between obesity and the risk of type 2 diabetes has been derived mainly from the analysis of the degree of obesity. The role of the duration of obesity as an independent risk has not been fully explored. The objective of the present study was to investigate the association between the duration of obesity and the risk of type 2 diabetes. Design: Prospective cohort study. Setting: The Framingham Heart Study (FHS), follow-up from 1948 to 1998. Subjects: A total of 1256 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
115
0
7

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(136 citation statements)
references
References 20 publications
10
115
0
7
Order By: Relevance
“…Previous studies showed that duration of obesity is an independent risk factor for adverse health outcome. 36,37 Therefore, establishing MHO individuals will require additional studies that observe longer enough and further assess obesity duration and weight history in depth. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that duration of obesity is an independent risk factor for adverse health outcome. 36,37 Therefore, establishing MHO individuals will require additional studies that observe longer enough and further assess obesity duration and weight history in depth. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 99%
“…Candidate mechanisms include hyperglycemia leading to joint tissue changes, particularly in collagen [27], and obesity leading to (1) increased mechanical load to the joint [31]; and/or (2) nonbiomechanical factors such as metabolism from increased fat [8,14,20,22]. Obesity is a risk factor for diabetes [1,15,17,19,30] and osteoarthritis [8,13,20,22,26], and both factors are increasing rapidly in the US population [6,10]. Unfortunately, data that might further explore these potential hypotheses are unavailable in our data set (BMI, HbA1c, adipokine biomarkers).…”
Section: Discussionmentioning
confidence: 99%
“…Considerando a influência da alimentação dos pais sobre as escolhas das crianças, é fácil perceber que os hábitos alimentares dos pequenos brasileiros estão apoiados sobre os pilares das escolhas inadequadas dos pais. Dessa forma, qualquer intervenção que busque reverter a crescente incidência da obesidade infantil precisa ser trabalhada juntamente com os responsáveis pela aquisição do gênero alimentício: os pais ou responsáveis (7,8) .…”
Section: Obesidade Infantil: O Problema De Saúde Pública Do Século 21unclassified
“…Sobrepeso e obesidade em crianças são o provável início da obesidade na idade adulta e também o início do desenvolvimento de doenças não transmissíveis como diabetes e doença cardiovascular. Sobrepeso e obesidade são doenças crônicas altamente preveníveis, mas a duração da obesidade é um fator de risco, independentemente do IMC na idade adulta (7,8) . Existe risco aumentado em 2,5 de mortalidade a cada duas décadas de obesidade do indivíduo (7) .…”
Section: Obesidade Infantil: O Problema De Saúde Pública Do Século 21unclassified